Empathy through Animals: Generating Evidence‐based Outcomes for Empathy Development. (1st December 2016) - Dawson, Jamie
Abstract: Low empathy is a prominent trait associated with juvenile offenders. Many juvenile justice service providers strive to reduce risk factors associated with juvenile delinquency, while producing evidence‐based outcomes for targeted programming. The Youth Services Agency (YSA) Nature Center provides empathy development through animal therapy to adjudicated youth. This project generates evidence‐based outcomes and quantifies the impact of animal therapy on empathy development of adjudicated youth at the YSA Nature Center by utilizing self‐assessment tools. Results indicated trends that animal therapy increases the emotional empathy of YSA clients. Qualitative evidence implied that animal therapy had notable therapeutic value to YSA clients.